Anti-Platelet Fraction Isolated from Galega Officinalis - Atanasov A. (Acta Medica Bulgarica, 2016)
A fraction from crude extract of Galega officinalis has been purified by column chromatography on Sephadex G-25, Sepharose 4B, DEAE-Cellulose and Sephadex G-100. The final purification factor of the fraction is 120. The peak in elution profile after Sephadex G-150 shows a molecular weight of 100-140 kDa. The isolated fraction appears to have 74% polysaccharides and 23% of proteins. No loss of activity of the final fraction is observed after storage for several months at 4°C and in lyophilized condition. The fraction compounds inhibit platelet aggregation induced by ADP, collagen and thrombin.